2022
DOI: 10.1039/d1ra08184e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of eugenol nanoemulsions for antibacterial activities

Abstract: We developed a novel eugenol nanoemulsion with high stability and good biological activity, which may provide a promising and effective method for wound treatment in the healthcare area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 53 publications
3
16
0
Order By: Relevance
“…A reduction in particle MDD with increasing OSR from 1:0.5 to 1:1 (199–154.94 and 134.5–115.9 nm for bath‐ and probe‐sonicated NEs, respectively), could be attributed to increased disruption force and decreased recoalescence force. The lower interfacial tension at the oil/water interface resulted in a highly dynamic interface that facilitated small droplet formation (Ghosh et al ., 2013; Fu et al ., 2022). However, the MDD was found to increase from 1:1 to 1:3 OSR (154.94–220.4 and 115.9–132.7 nm for bath‐ and probe‐sonicated NEs, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…A reduction in particle MDD with increasing OSR from 1:0.5 to 1:1 (199–154.94 and 134.5–115.9 nm for bath‐ and probe‐sonicated NEs, respectively), could be attributed to increased disruption force and decreased recoalescence force. The lower interfacial tension at the oil/water interface resulted in a highly dynamic interface that facilitated small droplet formation (Ghosh et al ., 2013; Fu et al ., 2022). However, the MDD was found to increase from 1:1 to 1:3 OSR (154.94–220.4 and 115.9–132.7 nm for bath‐ and probe‐sonicated NEs, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…ROS attacks the unsaturated fatty acids in cell membrane to form lipid peroxidation products, such as malondialdehyde, changing the fluidity and permeability of cell membrane. [69] Hong et al found that copper alloy-mediated E. coli death was mainly mediated by membrane lipid peroxidation. [70] Copper ion (Cu 2+ ) participate in the Fenton-like reaction to generate ROS.…”
Section: Interference Of Behaviors and Functionsmentioning
confidence: 99%
“…The preparation of usAgNPs-PL/CMC hydrogel First, whole blood was taken from the cardiac apex of rats, centrifuged at 3000 rpm for 20 min, then the upper layer was taken to obtain PL according to the previous report [22]. 0.5 g of usAgNPs was added to 10 ml of DMSO under ultrasonation for 45 min followed by the mixing with 10ml of PL.…”
Section: Cell Culturementioning
confidence: 99%
“…The centrifuge tube cover was heated at 95 ℃ for 40 min, cooled, then the samples were centrifuged at 12000r/min for 2 min, At last the absorbance value was determined at 532 nm. MDA content in bacterial cells were calculated according the report [22] .…”
Section: Detection Of Bacterial Intracellular Atpmentioning
confidence: 99%